Arterial Regeneration: Dimeric Thymosin β4 Loaded Nanofibrous Interface Enhanced Regeneration of Muscular Artery in Aging Body through Modulating Perivascular Adipose Stem Cell–Macrophage Interaction (Adv. Sci. 8/2020). Issue 8 (22nd April 2020) - Chen, Wanli; Jia, Sansan; Zhang, Xinchi; Zhang, Siqian; Liu, Huan; Yang, Xin; Zhang, Cun; Wu, Wei
Abstract : In article number 1903307, Cun Zhang, Wei Wu, and co‐workers identify the adult perivascular adipose tissue (PVAT) as the dominant source of vascular progenitors in a rat abdominal aorta model and clarify the mechanism by which DTβ4 enhances arterial muscle remodeling in the aging body. Different from conventional synthetic grafts, DTβ4‐incorporated grafts exhibit enhanced vascular regenerative activity and effectively ameliorate aging induced defective regeneration, thus providing a rational strategy for clinical translation of vascular grafts.